Flash Emissions from Acrylonitrile Storage Tank and Their Impact on Ambient Air Quality - Mapraditkul, Pornpavit; Jookjantra, Peemapat; Charuchitsopon, Pavaris; Premrungchet, Korn; Sooktawee, Sirapong; Thepanondh, Sarawut (Journal of Engineering and Technological Sciences, 2026)
Flash emissions from chemical storage tanks are a major source of volatile organic compounds (VOCs), accounting for over 90% of total VOC releases during storage. This study evaluated acrylonitrile emissions at a petrochemical facility using the Vasquez-Beggs Equation (VBE), TANKS 5.1, and the AERMOD dispersion model. Under midrange conditions, flashing losses were estimated at 12.84 g/s, with peak emissions reaching 18.17 g/s under high-pressure, low-temperature conditions. In comparison, breathing and working losses contributed only 0.0986 g/s and 0.2776 g/s, respectively, in uncontrolled scenarios. Air dispersion modeling indicated acrylonitrile concentrations exceeding 800 µg/m³ for 24-hour exposure and surpassing 250 µg/m³ in annual averages near sensitive receptors under uncontrolled conditions. Implementing a 90% efficient emission control system reduced flashing losses to 1.284 g/s, effectively lowering ambient concentrations by more than 80%. However, even with substantial reductions, residual cancer risks at certain receptors remained above the acceptable threshold of 1.0 × 10⁻⁶, highlighting the need for additional mitigation measures. These findings underscore the importance of advanced emission control technologies and optimized operational practices to minimize the environmental and health impacts of acrylonitrile storage tanks, offering actionable insights for sustainable industrial air quality management.